UNIVERSITIES OF ANCIENT GREECE - Walden, John William Henry, 1864- Link ([S.l.])
1 online resource
Keywords: The Universities of Ancient Greece (1912) examines Greek education in the Classical world, from the pre-Alexandrian times to the last three centuries B.C. Universities' are defined as congregations of professors and students, as well as the organized bodies at places such as Alexandria (at the Museum), the Capitolium at Constantinople, at Athens and Antioch.